Effect of Light Exposure on Functional Compounds of Monovarietal Extra Virgin Olive Oils and Oil Mixes During Early Storage as Evaluated by Fluorescence Spectra - Diaz, Gabriela Esther; Pega, Juan Franco; Primrose, D.; Sancho, Ana Maria; Nanni, Mariana (Springer, 2019)
The oxidation of antioxidants in bottled extra virgin olive oil (EVOO), especially vitamin E and chlorophyll, can affect the quality of the product. However, the effect of light exposure on these functional compounds and their relation with oil quality, during the early storage of EVOO, is not clear. In this study, we evaluated the photochemical stability of vitamin E and chlorophyll in two monovarietal EVOO, Picual (PEVOO) and Farga (FEVOO), and in mixed olive oils (MOO) containing 70:30 v/v of EVOO and sunflower oil (SO), respectively. PEVOO, FEVOO, MOO and SO were subjected to light exposure for 7 days, and the amounts of vitamin E and chlorophyll were assessed by fluorescence spectra. Peroxide value (PV) and acidity index (AI) were also determined. Results showed that MOO contained significantly lower contents of vitamin E and chlorophyll than PEVOO or FEVOO before light exposure (p < 0.001). However, these compounds showed a significant decrease in PEVOO and FEVOO throughout light exposure (p < 0.001). Interestingly, although the effect of oil variety and light exposure on PV and AI determinations was significant (p < 0.001), all the oils showed values which were in accordance with the International Olive Council (IOC) standards. Principal component analysis (PCA) highlighted antioxidant changes in EVOO, MOO and SO upon this short period of light exposure. As a whole, our results indicate that, unlike PV and AI determinations, fluorescence spectra analysis may be an interesting tool for quality control in EVOO mixed with other oils or subjected to inadequate storage conditions.